2009
DOI: 10.1542/peds.2008-1146
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Children Is Associated With Increased Risk of Asthma

Abstract: This study provides evidence that the use of antibiotics in the first year of life is associated with a small risk of developing asthma, and this risk increases with the number of courses of antibiotics prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(225 citation statements)
references
References 19 publications
13
206
1
5
Order By: Relevance
“…5,9 The high prescription rate of antibiotics in all age groups in our study is also consistent with other reports. 1,10 In a study performed by Marra et al 10 to investigate the association of antibiotic use to later asthma development, 43.3% of the subjects aged up to 9 years were treated with antibiotics over the course of a year. This percentage is somewhat lower than our finding that 58.27% of Belgian children younger than 8 years were treated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 The high prescription rate of antibiotics in all age groups in our study is also consistent with other reports. 1,10 In a study performed by Marra et al 10 to investigate the association of antibiotic use to later asthma development, 43.3% of the subjects aged up to 9 years were treated with antibiotics over the course of a year. This percentage is somewhat lower than our finding that 58.27% of Belgian children younger than 8 years were treated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, perinatal use of antibiotics, particularly in premature infants, can interfere with the balance of bacterial phyla and diversity of individual species and makes the newborn much more susceptible to infectious inflammatory diseases (10,11). Long-term follow up on the use of antibiotics during the first year of life has shown an association with an increased incidence of inflammatory bowel disease (12), asthma (13), and increased weight gain leading to adult obesity (14). These studies suggest that optimal initial colonization is critical in the adjustment of the newborn to the extrauterine environment.…”
Section: Initial Colonizationmentioning
confidence: 99%
“…Antibiotic use during pregnancy and in infants and toddlers has been associated with the development of asthma later in life, [522][523][524] although not all studies have shown this association. 525 Intake of the analgesic, paracetamol (acetaminophen), may be associated with asthma in both children and adults, 526 although exposure during infancy may be confounded by use of paracetamol for respiratory tract infections.…”
Section: Medications and Other Factorsmentioning
confidence: 99%